Relationship Between Healthy Habits and Perceived Motivational Climate in Sport Among University Students: A Structural Equation Model - Cofre-Bolados, C (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
(1) Background: Several studies have shown how certain types of motivation for sports can favour healthy habits or can cause risk behaviours. (2) Methods: The aim of this study was to establish and verify an explanatory model for motivational climate in sport which considers other possible influential variables related to health. This research was conducted with a sample of 490 university students from Spain. The 33-item Perceived Motivational Climate in Sport Questionnaire (PMCSQ-2) was used to assess perceived motivational climate. The Alcohol Use Disorders Identification Test (AUDIT), the Questionnaire of Experiences Related to Video Games (QERV), the Physical Activity Questionnaire for Adolescents (PAQ-A), and the KIDMED test were used to assess healthy habits; (3) Results: Findings revealed that task-involved climate and ego-involved climate were both positively associated with physical activity with the strongest relationship emerging for a task-involved climate. Furthermore, task climate was positively associated with a good adherence to aMediterranean diet. A direct relationship was found between ego climate and alcohol intake and problematic use of video games; (4) Conclusions: The findings imply that students who have greater intrinsic motivation to participate in sport and perceive a task-involved climate also report healthier habits. This highlights the importance of creating task-involved motivational climates in sport and physical education lessons. © 2018 by the authors.